Perlindungan Hak Perempuan Dalam Keluarga Menurut Hukum Islam: Analisis Kasus Diskriminasi Gender - Dahlianatalia Lumban Gaol; Fani Nolpiana Nadapdap; Grace Michael Sihombing; Tasya Br Marbun; Widya Helen A. Purba; Sri Hadiningrum (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2024)
This research discusses how women's rights in the family are protected according to Islamic law in analyzing gender discrimination cases. This study was conducted to determine gender inequality in several aspects of life, such as inheritance and inheritance. It is hoped that this research can contribute to a better understanding regarding making an important contribution in expanding understanding of the Islamic legal perspective on gender equality, which can become a reference for policy makers in promoting gender equality in Muslim societies. The research method is to use a literature study research method which includes Islamic legal discrimination in various social and geographical contexts. Public education regarding women's rights in Islam is an important key to changing perceptions and reducing gender discrimination. Legal reforms that support gender equality need to continue to be developed to create more effective protection of women's rights.